Curriculum development for project-based engineering education: how to include soft skills - Hattum, Natascha Janssen Van (2007)
The implementation of project-lead engineering course at the university of Minho, lead to a number of questions on curriculum design for the inclusion of solft skills in the curriculum. Project lead education avoids fragmentation of content into separet subject that are not clearly connected and is recognised as a way to provide a coherent course program. Student work in teams on the solution of an existing engineering problem that reflects their future professional practice and integrates tecnical competencies of different scientific areas. Not only they have to fulfil the requirements ofcthe project and show that have found a feasible solution for the problem, they also have to show that they have obtained the competencies in different subject areas that are related to the project. this kind of education asks for the developed of skills that are less emphasised in traditional education, like team work and comumunication skills, and involves a much more integrated problem approach compared to a system in which subjects are taught is isolated parts